2012
DOI: 10.5812/iranjradiol.8065
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to Newborns in Neonatal Intensive Care Units

Abstract: BackgroundWith the increase of X-ray use for medical diagnostic purposes, knowing the given doses is necessary in patients for comparison with reference levels. The concept of reference doses or diagnostic reference levels (DRLs) has been developed as a practical aid in the optimization of patient protection in diagnostic radiology.ObjectivesTo assess the radiation doses to neonates from diagnostic radiography (chest and abdomen). This study has been carried out in the neonatal intensive care unit of a provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 10 publications
1
23
2
Order By: Relevance
“…The results of this study showed that the calculated ESD of different organs was greater than those reported in other studies in Iran including Kashan and Mashhad (3,18). Nevertheless, these values were lesser than those reported in other parts of Iran, Chaharmahal and Bakhtiari (19), Shiraz (14), (20) and Esfahan (7).…”
Section: Discussioncontrasting
confidence: 54%
“…The results of this study showed that the calculated ESD of different organs was greater than those reported in other studies in Iran including Kashan and Mashhad (3,18). Nevertheless, these values were lesser than those reported in other parts of Iran, Chaharmahal and Bakhtiari (19), Shiraz (14), (20) and Esfahan (7).…”
Section: Discussioncontrasting
confidence: 54%
“…Our findings showed that the rate of uptake in the G1 is a little less than the Ch1 and the T1. In their study in 2012, Toossi et al reported an ESD rate of 85.191 µG in the infant’s chest [13]. …”
Section: Discussionmentioning
confidence: 99%
“…As the sensitivity of cells towards ionising radiation depends on the rate of mitosis of cells, those cells with a high rate of mitosis are more sensitive towards damage caused by ionising radiation because the mitosis growth rate of cells in children is up to 10 times higher than in adults, so their cells are also more sensitive to ionising radiation. The highest sensitivity towards ionising radiation is found in newborns and decreases with age 10 . Another feature in children is that the endogenous mechanisms to control damage caused by radiation is not fully mature and therefore less effective compared to adults.…”
Section: Discussionmentioning
confidence: 99%